Identification of Local Chicken Farmersâ Behavior in Adopting Innovation of Technology Intensification - Setiana, L; Isbandi, Isbandi; Atmomarsono, Atmomarsono; Waridin, U (ANIMAL PRODUCTION, 2012)
This research aimed to identify behavior of adopting technology innovation of local chicken farmers in Banyumas. Qualitative approach was applied to get a further examination on farmersâ characteristics and pattern of adopted maintenance system while domain, taxonomy and component analysis were further applied in accordance to innovation as the main goal. Purposive Random Sampling was used to determine 176 respondents from six groups of local chicken farmers in five selected sub districts. Result showed that maintenance systems applied by the farmers were traditional maintenance (39.77%), semi-intensive (52.27%), and intensive (7.96%). Intensification workshop, in conclusion did not always meet the result expectancy since many farmers still applied traditional and semi-intensive system.Keywords: adoption behavior, technology innovation, intensification, local chicken farmersÂ Animal Production 14(2):118-122